Ocular Syphilis and Human Immunodeficiency Virus Co-infection: A Case Report - Segu, Bhagya; Huang, Yun-Ting Lisa; Alexander, Justin; Leung, Theresa; Breaux, Katharine (Canadian Journal of Optometry, 2025)
Ocular syphilis is a rare complication of syphilis, a sexually transmitted disease caused by the spirochete bacterium Treponema pallidum. Syphilis is a diagnostic challenge due to its diverse and often subtle clinical manifestations. We report a patient with no known history of sexually transmitted infections (STIs) who presented with sudden onset reduced vision and mutton fat keratic precipitates (KPs). Serological testing subsequently confirmed the diagnosis of syphilis and human immunodeficiency virus (HIV) co-infection. This case highlights the insidious nature of ocular syphilis and emphasizes the importance of a comprehensive ophthalmic evaluation and prompt treatment.